Razvoj slovenistične didaktike književnosti - Krakar-Vogel, Boža (Slavistična revija, 2013)
During the last quarter of a century the didactics of literature has become a formal subject in higher education at the University of Ljubljana's Filozofska fakulteta. This article contains a brief overview of epistemological and content questions in the subject from its beginnings to the present, as well as the kinds of problems researchers in the department have dealt with in their publications. The discipline of teaching literature had a pre-academic phase in the theoretical and applied reflections of practitioners in the nineteenth and twentieth centuries. Contemporary didactics of literature as a research discipline has been able to make use of these since the 1980s.
Keywords: aims and objectives of education; cilji; didactic method; didactics; didaktika; književnost; literature; Slovene literature; slovenska književnost; visokošolski študij